Taxonomy of 'Euconnus complex'. Part VI. Status of Protoscydmus and Euconnus subgenera Neonapochus, Paranapochus, and Filonapochus (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
Examination of the type species of the genus Protoscydmus (Borneo) and subgenera of Euconnus: Neonapochus (Europe) and Paranapochus (Madagascar, Oriental) revealed that these taxa do not differ in any important characters from Euconnus (Napochus). Consequently, Protoscydmus, Neonapochus, and Paranapochus are placed as junior synonyms of Napochus, and Euconnus (Napochus) sabahensis (Franz) is placed as a new combination (ex Protoscydmus). Filonapochus (Madagascar) is maintained as a separate subgenus of Euconnus; it also belongs to taxa similar to Napochus.